Encouraging Collaboration and Teamwork in Learning - Rustamova, Sevinch (Journal of Innovation in Education and Social Research, 2025)
Collaboration and teamwork have become indispensable in modern education as they prepare learners for both academic and professional success. This article examines strategies for enhancing collaborative learning, explores methods that encourage teamwork, and discusses the outcomes of such approaches in diverse educational contexts.